The CDEP scheme: administrative and policy issues - Altman, Jon; Sanders, Will
The Community Development Employment Projects (CDEP) scheme is a program whereby Aboriginal community councils receive grants roughly equivalent to the social security entitlements of community members which are used as wages for the creation of jobs. It has been operating since 1977, during which time it has expanded to include 169 participating communities and involve 18,266 Aboriginal people. Expenditure on CDEP for 1990-91 totalled about $194 million, representing 36 percent of the Aboriginal Affairs portfolio expenditure. This paper focuses on the nature of some unresolved administrative and policy issues relating to the CDEP scheme. Many of these issues stem from the development of the DCEP scheme as both
Keywords: Social Security Unemployment; Employment; Community Development Employment Projects Scheme; Community Development; Community Development - Employment - Australia